Peran Pendidikan Islam di Era Globalisasi Perspektif Hadis - Khoirunnisa Khoirunnisa; Fitriani Fitriani (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about the role of Islamic education. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the role of Islamic education in the history of Ahmad No. 7965. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Ahmad No. 7965 is relevant to be used as motivation in studying.